Evaluation of the Antigen-Experienced B-Cell Receptor Repertoire in Healthy Children and Adults - IJspeert, Hanna; van Schouwenburg, Pauline A.; van Zessen, David; Pico-Knijnenburg, Ingrid; Driessen, Gertjan J.; Stubbs, Andrew P.; van der Burg, Mirjam (Frontiers in Immunology, 2016)
Upon antigen recognition via their B cell receptor (BR) B cells migrate to the germinal center where they undergo somatic hypermutation (SHM) to increase their affinity for the antigen, and class switch recombination (CSR) to change the effector function of the secreted antibodies. These steps are essential to create an antigen-experienced BR repertoire that efficiently protects the body against pathogens. At the same time, the BR repertoire should be selected to protect against responses to self-antigen or harmless antigens. Insights into the processes of SHM, selection and CSR can be obtained by studying the antigen experienced BR repertoire. Currently, a large reference data set of healthy children and adults, which ranges from neonates to the elderly, is not available. In this study, we analyzed the antigen-experienced repertoire of 38 healthy donors (HD), ranging from cord blood to 74 years old, by sequencing IGA and IGG transcripts using next generation sequencing. This resulted in a large, freely available reference data set containing 412,890 IGA and IGG transcripts. We used this data set to study mutation levels, SHM patterns, antigenic selection and CSR from birth to elderly HD. Only small differences were observed in SHM patterns, while the mutation levels increase in early childhood, and stabilize at six years of age at around 7%. Furthermore, comparison of the antigen-experienced repertoire with sequences from the naïve immune repertoire showed that features associated with auto-immunity such as long CDR3 length and IGHV4-34 usage are reduced in the antigen experienced repertoire. Moreover, IGA2 and IGG2 usage was increased in HD in higher age categories, while IGG1 usage was decreased. In addition, we studied clonal relationship in the different samples. Clonally related sequences were found with different subclasses. Interestingly, we found transcripts with the same CDR1-CDR3 sequence, but different subclasses. Together these data suggests that a single antigen can provoke a B-cell response with BR of different subclasses, and that during the course of an immune response some B cells change their isotype without acquiring additional SHM, or can directly switch to different isotypes.